2009
DOI: 10.1007/s00244-009-9321-z
|View full text |Cite
|
Sign up to set email alerts
|

Acetate Enhances the Specific Consumption Rate of Toluene Under Denitrifying Conditions

Abstract: Toluene is usually present in the environment as a contaminant along with other carbon sources which may influence its removal. In this work we studied the effect of a readily consumable carbon source such as acetate on toluene mineralization under denitrifying conditions. Continuous and batch cultures with stabilized denitrifying sludge were carried out. An upflow anaerobic sludge blanket reactor (UASB) was fed with several ratios of acetate-C/toluene-C loading rates (mg C/L-day: 100/0, 75/25, 50/50, and 0/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
1
17
0
9
Order By: Relevance
“…The temperatures of the column, injector and detector were 50, 100 and 100 • C, respectively, with helium as the carrier gas at 16 mL min −1 . Acetate concentration was determined by gas chromatography (Hewlett Packard 5890, USA) as previously described by Martínez-Hernández et al [19]. Organic and inorganic carbon was determined using a total organic carbon (TOC) analyser (Shimadzu, TOC-VCSN, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperatures of the column, injector and detector were 50, 100 and 100 • C, respectively, with helium as the carrier gas at 16 mL min −1 . Acetate concentration was determined by gas chromatography (Hewlett Packard 5890, USA) as previously described by Martínez-Hernández et al [19]. Organic and inorganic carbon was determined using a total organic carbon (TOC) analyser (Shimadzu, TOC-VCSN, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Sanford and Tiedje [23] proposed that, under denitrifying conditions, 2-CP consumption is initiated by the reduction of 2-CP to phenol and requires the addition of an electron donor such as acetate to initiate the dehalogenation process. It has been also suggested that the addition of readily oxidable carbon sources might improve the consumption of recalcitrant aromatic compounds [10,19]. To obtain a better understanding about how 2-CP consumption could be improved under denitrifying conditions, phenol and acetate were tested as co-substrates.…”
Section: -Chlorophenol Consumption At Stoichiometric C/n Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3(b) shows the influent and effluent TOC change in UASB with a high carbon concentration and a high nitrogen loading rate. Sodium succinate [12,28] was the only carbon source in the denitrification process, and the detected gas did not contain carbon dioxide, which might be produced in the reactor. The average TOC difference between influent and effluent was 72.02 mg L ¡1 , which can be used by denitrification organisms under anoxic conditions in UASB.…”
Section: Cod Removal Rate and Toc Change During The Set-up Processmentioning
confidence: 99%
“…The glucose concentration was determined using a YSI 2700 biochemical analyzer (YSI-2700 Select, USA) with a YSI membrane 2365. Acetate concentration was quantified by gas chromatography (Hewlett-Packard 5890, USA) using a flame ionization detector and a steel packed column (Porapak Q Mesh 80-100, USA) [28]. Soluble organic and inorganic carbon was measured in a total organic carbon (TOC) analyzer (Shimadzu, TOC-VCSN, Japan).…”
Section: Batch Assaysmentioning
confidence: 99%